Género y cine: estudio de caso de las películas “LA TIGRA Y A TUS ESPALDAS” - Varela Molina, Katherin Patricia (2020)
The present research is to identify what gender stereotypes are present in Ecuadorian film productions: "La Tigra," by Camilo Luzuriaga and "A Tus Espaldas" by Tito Jara, this research has a methodology with a qualitative approach, that allows to examine interpretations of the current content, in which selected scenes and dialogues will be taken that are exhibited in the two films, evidencing and analyzing the content that Ecuadorian cinema transmits and creates. After reviewing the history of Ecuadorian cinema and analyzing the legislation governing national production as the theoretical basis of the investigation aimed at generating a critical look at the viewer on the quality of the content of the cinematographic films "La Tigra” and "A Tus Espaldas". Productions where it is possible to define that the contents reproduce the gender stereotypes of the time. But at the same time, they manage to project the evolution of Ecuadorian thought and to shape on the big screen to the future that will sustain the collective thinking about the role that men and women must play in society. The results presented at the end of the research provide the viewer with clear and stereotypical information that allows to make a more critical assessment of the films.